Species-specific N-glycan patterns in animal and human breast milk samples - Ret, Davide; Gentile, Salvatore Alessio; Rohrhofer, Johanna; Koidl, Larissa; Cozzi, Francesca; Untersmayr, Eva (Frontiers in Nutrition, 2025)
The main components of milk are protein, fat and carbohydrates. Glycans are complex carbohydrate structures covalently bound to proteins and lipids or exist freely in solutions. The function of glycans in nature is to contribute to structure, energy metabolism and encoding relevant biological information. In this study we have analyzed the content of sialic acids. Moreover, we assigned and compared the N-glycan profile of the milk casein and whey fraction from humans, infant formula, cows, horses, goats, and sheep. Conservation of terminal sialic acids on the glycan structures was achieved by stabilization via methylamidation. Human breast milk exhibitsa unique glycan profile, characterized byhighly fucosylated N-glycans and is rich in N-acetylneuraminic acid (Neu5Ac), while N-glycolylneuraminic acid (Neu5Gc), a sialic acid not synthesized in humans, was not detected. In contrast, other mammalians are characterized by a species-specific N-glycan profile with low amounts of fucosylated glycans and different amounts of Neu5Gc. Sheep’s milk has the highest amount of Neu5Gc, followed by goat’s milk, horse’s milk, and cow’s milk. In infant formula, the concentration of total sialic acid is reduced in comparison to human breast milk and contains approximately 7% of the non-human sialic acid Neu5Gc. Regarding the analysis of N-glycan profiles comparing casein and whey fractions, no differences were observed for human breast milk, only marginal differences for cow, horse, goat and sheep and pronounced differences in infant formula. Our work confirms that human breast milk has a unique N-glycan signature with a distinct glycan composition when compared to all other mammalian milk samples. No traces of the non-human sialic acid Neu5Gc were detected, whereas it was found in varying amounts throughout the other milk samples.